Melnik Ju. P. Actual aspect of polypredicative sentence in the English literary discourse - Melnik Ju. P. (Philological Treatises, 2020)
The article deals with functional perspective of a complex sentence in English discourse. The functional perspective of a complex sentence is distinguished here at two levels: microlevel andmacrolevel. Theme and rheme structural patterns are represented by such types of connection: parallel, chain-type, parallel-chain-, and ray-type. The communicative intention of a speaker is reflected in theme-rheme structure of each sentence part. It is stated that a clause is a centre of communicative stress.